Analyzing Expressions of the Design Argument and Answering Doubts Attributed to it Based on the Type of Logical Reasoning - Shokoh Monazzam; Abbas Abbaszadeh; Naser Forouhi (Comparative Theology)
The design argument is one of the simplest and most common arguments that connects humans to the material world. Since a long time ago, humans have acknowledged the existence of wise and intelligent moderators through thinking about the structure of creatures and their purposiveness. Various expressions of this argument with different degrees of strength and accuracy are seen in the talk of Islamic and Western thinkers who through argument, analogy, or induction and with dependence on partial or general instances of design in nature are trying to prove an intelligent moderator. Correct perception of this argument and a correct analysis of its preliminaries based on intellect can increase its validity and reliability in proving divine moderator and help us to answer the main part of doubts attributed to it. This descriptive-analytical study considers doubts attributed to this argument from an epistemology viewpoint and tries to eliminate and answer them by explaining the position and role of intellect in this argument relying on conditions of various logical reasons, and defending its validity and reliability in proving meta-matter moderator and abrogating materialists’ opinion. Keywords: Order; Intellect; Purposiveness; Science; Divine Moderator.Introduction The current research has assessed the design argument and doubts attributed to it. Understanding the position of intellect in this argument and basing its preliminaries on intellectual principles and fundamentals can help us reach a correct perception of this argument and answer doubts propounded by critics. The most important aspect of this study is answering some doubts propounded as a result of the incorrect perception of this design with its various expressions. What distinguishes the current study from other works related to this subject is that it separates doubts attributed to its major and minor aspects by focusing on logical reasoning in terms of argument, induction, and analogy. Materials and Methods This study analyzes the design argument and its expressions and tries to answer doubts attributed to this argument relying on conditions of logical reasoning. In the past, two expressions based on similarity and replication in talks of Western philosophers were common and these expressions have received a lot of critiques according to their weakness. While these expressions mainly differ from the design argument in terms of rational reasoning. From an epistemology viewpoint, order isn’t from sensory concepts and human senses cannot perceive order directly, but it is an empirical concept, and order of nature can be induced based on experience and by getting help from some intellectual preliminaries. In addition, an intellectual movement from the purposive order of nature toward aware creatures is performed not in terms of analogy and replication with human artifacts but based on intellectual principles like cause-effect suitability. Research FindingsThe most important aspect of the design argument is that the purposive order of the world indicates the intervention of awareness and intelligence in its creation and such an order cannot be explained through unconscious factors including intrinsic characteristics of matter. In this argument, it is claimed that order, harmony, and purposiveness indicate the intervention of intelligence in the combination of the world, nature, and matter and components of the world cannot explain the final order while accepting the natural and intrinsic nature of matter. Therefore, design order should prove that the existence of purpose in the world of nature, and its random emergence refusal indicates that the world moderator has characteristics of science and power. In other words, an intelligent and powerful actor has created the world. Therefore, proving sanity and or god of religions, especially Islam, with all perfection attributes, is not in the scope of this argument. In addition, its validity cannot be questioned; empirical scientific validity is based on the hidden analogy that has accompanied and supported it. Therefore, the design argument has intellectual preliminaries (directly or indirectly). Discussion of Results and Conclusion The design argument connects the human mind with beyond physical world relying on relation and logical correlation between purposive order and intellect intervention. On the one hand, the interaction existed between intellect and experience in the design argument, and on the other hand, disability for correct analysis of this relation has caused the creation of expressions of this argument that differ with what is the main purpose of this reasoning under the title of “design order”. The design argument is not a sensory argument with all preliminaries originating from sense nor an empirical argument in which induction is performed based on analogy. However, it is an intellectual argument that a person infers the intervention of intellect and intelligence by studying the order of nature in natural creatures. Therefore, real believers would not conclude the existence of a contriver creature in the design argument based on knowing the world as a mechanical one but perceive an intelligent cause based on definite and obvious rules like causality and cause-effect suitability.